Open innovation for libraries using linked open data technologies - Saorín, Tomás (Anuario ThinkEPI, 2012)
The importance for libraries, archives and cultural heritage institutions of open innovation on the basis of linked open data basis is discussed. As the web evolves into a global data space, libraries should provide their datasets using RDF technologies and open licenses to strengthen innovative services developed by third parties reusing their metadata and digital contents.
Keywords: Linked open data; Open innovation; Libraries; Information reuse.